Challenges Faced by Teachers and Students of Islamabad Postgraduate Colleges during Covid-19 - Malka Fareeha Azhar; Dr. Wajiha Kanwal; Khola Thaira (Journal of Management Practices, Humanities and Social Sciences, 2022)
The study aimed to examine the challenges faced by teachers and students at Islamabad Postgraduate Colleges during COVID-19. The main objectives of the study were to examine the challenges faced by teachers during COVID-19, analyze the challenges faced by students during COVID-19, and compare the challenges of teachers and students during COVID-19. In Islamabad; there were seven postgraduate colleges for women. The population of this study consists on all the teachers and students of these colleges. Using Gay’s suggestion, the researcher selected 10% of the teachers and 10% of students through random sampling technique for the purpose of data collection. In order to measure the variables, research instruments (questionnaires) for teachers and students were developed. Data were collected through questionnaires, and the SPSS software was used to tabulate, analyze, and interpret the data. The mean, median, percentages, and t-test were used to look at the data in light of the study's goals. The findings of the study were analyzed on the basis of categories. It was concluded that the COVID-19 pandemic greatly affected the teaching and learning processes of the Islamabad Postgraduate Colleges. Teachers were facing challenges in the online teaching process during the COVID-19 pandemic. It has negatively impacted on the students’ satisfaction levels towards their studies. The study explored an unprecedented situation and the challenges it brought. The use of internet and online mode of learning was totally new to this population. The knowledge of these problems makes this study significant for helping in defining scope of online learning in futuristic perspective.